2021
DOI: 10.1186/s12890-021-01736-8
|View full text |Cite
|
Sign up to set email alerts
|

Hospital admission trends due to respiratory diseases in England and Wales between 1999 and 2019: an ecologic study

Abstract: Background Identifying trends of hospital admissions for respiratory diseases is crucial for public health and research to guide future clinical improvements for better outcomes. This study aims to define the trends of respiratory disease-related hospital admissions (RRHA) in England and Wales between 1999 and 2019. Methods An ecological study was conducted using hospital admission data taken from the Hospital Episode Statistics database in Englan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
27
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

5
4

Authors

Journals

citations
Cited by 32 publications
(31 citation statements)
references
References 35 publications
4
27
0
Order By: Relevance
“…Previous studies in Denmark, Sweden, and Norway explored the utilisation pattern of different classes of medications such as opioids and antiarrhythmic medications and reported an increase in their utilisation [ 33 35 ]. Recent studies in the UK showed an increase in hospitalizations for various acute and chronic conditions, such as viral diseases, respiratory diseases, and heart diseases [ 19 , 36 , 37 ]. Raised hospitalisation rates highlight that there is an increase in the prevalence of these diseases that lead to hospitalisation, which itself could lead to an increase in the prescribing pattern of medications.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies in Denmark, Sweden, and Norway explored the utilisation pattern of different classes of medications such as opioids and antiarrhythmic medications and reported an increase in their utilisation [ 33 35 ]. Recent studies in the UK showed an increase in hospitalizations for various acute and chronic conditions, such as viral diseases, respiratory diseases, and heart diseases [ 19 , 36 , 37 ]. Raised hospitalisation rates highlight that there is an increase in the prevalence of these diseases that lead to hospitalisation, which itself could lead to an increase in the prescribing pattern of medications.…”
Section: Discussionmentioning
confidence: 99%
“…The HES database provides detailed information on hospital admissions associated with a wide range of health conditions in England, and the PEDW provides similar information related to Wales residents [13][14][15][16][17][18][19]. The HES database's patient admitted care data includes all NHS-paid admissions to private or nonprofit hospitals.…”
Section: Data Sources and Study Populationmentioning
confidence: 99%
“…Considering age group variations in NRHA, the age group 60-74 years accounted for 38.5% of the total number of NRHA, followed by the 15 2).…”
mentioning
confidence: 99%
“…As previously described [9][10][11], we conducted an ecological study using publicly available data extracted from the Hospital Episode Statistics (HES) database in England and the Patient Episode Database for Wales (PEDW) between April 1999 and April 2019 [12,13]. The HES and PEDW databases contain hospital admission data for patients with B&ID from all age groups, which are subdivided into four categories -below 15 years, 15-59 years, 60-74 years, and 75 years and above.…”
Section: Study Sources and The Populationmentioning
confidence: 99%